2007
DOI: 10.1158/1078-0432.ccr-06-1662
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the Administration of High-Dose Interleukin-2 on Immunoregulatory Cell Subsets in Patients with Advanced Melanoma and Renal Cell Cancer

Abstract: Purpose: High-dose recombinant human interleukin-2 (IL-2) therapy is of clinical benefit in a subset of patients with advanced melanoma and renal cell cancer. Although IL-2 is well known as aT-cell growth factor, its potential in vivo effects on human immunoregulatory cell subsets are largely unexplored. Experimental Design: Here, we studied the effects of high-dose IL-2 therapy on circulating dendritic cell subsets (DC), CD1d-reactive invariant natural killerT cells (iNKT), and CD4 + CD25 + regulatory-typeTce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 31 publications
4
41
0
2
Order By: Relevance
“…Importantly, CD1d was predominantly expressed by mDC1 (Fig. 1B), confirming earlier reports (23,25), and expression levels were found to be comparable in healthy controls and cancer patients ( p ϭ 0.65). As the CD1d Ag-presenting molecule is required for the presentation of glycolipid Ag to iNKT cells, mDC1 were selected for additional experiments.…”
Section: Frequency and Expression Of Cd1d On Circulating DC Subsetssupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, CD1d was predominantly expressed by mDC1 (Fig. 1B), confirming earlier reports (23,25), and expression levels were found to be comparable in healthy controls and cancer patients ( p ϭ 0.65). As the CD1d Ag-presenting molecule is required for the presentation of glycolipid Ag to iNKT cells, mDC1 were selected for additional experiments.…”
Section: Frequency and Expression Of Cd1d On Circulating DC Subsetssupporting
confidence: 90%
“…Induction of IFN-␥ from iNKT and IL-12 from DC can act as a "positive feedback loop" and drive Th1 responses (1, 2, 18 -22). We recently showed that the circulating human CD1d ϩ DC subset, mDC1, responds like iNKT to high-dose IL-2 treatment, whereas CD4 ϩ CD25 ϩ regulatory type T cells behaved reciprocally (23). We hypothesized that the reported quantitative and/or qualitative differences in the circulating DC of cancer patients could contribute to the observed defects in iNKT cells and we therefore compared interactions between iNKT cells and CD1d-expressing circulating DC from healthy donors and patients with advanced cancer.…”
Section: T He Cd1d-restricted Invariant Nkt (Inkt)mentioning
confidence: 99%
“…17,[33][34][35] Analysis of patients in the present trial who received NMA alone revealed that the number of IL-2 doses was strongly associated with the total number of CD4 ϩ Tregs, but only moderately to weakly associated with the percentages of CD4 ϩ Tregs in the peripheral blood at week 1 ( Figure 5A first column). The number of IL-2 doses appeared to be weakly to moderately associated with peripheral CD4 ϩ Treg reconstitution in the 2-Gy trial, but were not associated with CD4 ϩ Treg reconstitution in the 12-Gy trial, perhaps as a consequence of the significant depletion of peripheral CD4 ϩ Tregs observed in patients receiving TBI ( Figure 5A).…”
Section: Association Between Number Of Administered Il-2 Doses and CDmentioning
confidence: 70%
“…Preferential activation of CD8 ϩ T cells or Tregs by IL-2 is not strictly dependent on the dose of IL-2 (ie, lower and higher doses of IL-2 can activate both) but rather depends on the preactivation status of CD8 ϩ cells because resting peripheral T cells do not express the high-affinity trimeric IL-2R until activated by specific antigens. [117][118][119][120] When CD8 ϩ CTLs are already active and express CD25, IL-2 may preferentially augment CTLmediated responses rather than Treg-mediated responses and thus can exacerbate GVHD. However, in vivo models suggests that a greater level of local IL-2 in conditions such as inflammation may promote the induction of nTreg cell function and subsequently inhibit clonal expansion and function of Teffs.…”
Section: Obstacles and Questions Facing Treg Researchmentioning
confidence: 99%